Inter-religious feelings of Sunni and Alevi Muslim minorities: The role of religious commitment and host national identification. (May 2016) - Martinovic, Borja; Verkuyten, Maykel
Abstract: This paper examines inter-religious attitudes from the perspective of Muslim minorities living in Western Europe. We examine both Sunni and Alevi Muslims of Turkish origin living in Germany and the Netherlands, and focus on their global feelings towards multiple religious out-groups (Christians, Jews, Muslim out-group, and non-believers). We hypothesize that Sunnis would dislike religious out-groups more than Alevis, and that these group differences in religious out-group feelings can be explained by group differences in host national identification and the three B's of religious commitment: belonging (religious identification), behaviour (religious practices), and belief (liberal values). Sunnis were found to be rather negative towards Alevis, and Alevis were even more negative towards Sunnis. Furthermore, as expected, Alevis had more positive feelings towards Christians, Jews and non-believers, and this was related to their stronger host national identification, lower religious group identification, lower involvement in religious practices, and stronger endorsement of liberal values. We conclude by pointing at the need to distinguish between subgroups of Muslims instead of treating them as a uniform collective.